Historical dictionary of organized labor - Velden, Jacobus Hermanus Antonius van der, 1954- (Historical dictionaries of religions, philosophies, and movements series, 2021)
"Historical Dictionary of Organized Labor: Fourth Edition makes the history of this important feature of life easily accessible. The reader is guided through a chronology, an introductory essay, 600 entries on the subject, appendixes with statistical material, and an extensive bibliography including Internet sites. This book gives a thorough introduction into past and present for historians, economists, sociologists, journalists, activists, labor union leaders, and anyone interested in the development of this important issue"--